A Simple Colorimetric Probe for Sensitive Detection of Hg2+ Based on MnO2 Nanosheets and Monothioglycerol. Issue 44 (23rd November 2020) - Ding, Lu; Zhao, Yanyu; Li, Huihui; Zhang, Qiujuan; Yang, Weiting; Pan, Qinhe
Abstract: It is of great significance to develop efficient platforms for the detection of hypertoxic Hg 2+ . Colorimetric probes have received much attention for the detection of Hg 2+ in the last decades. In this work, a colorimetric probe composed of MnO2 nanosheets and monothioglycerol (MTG) was rationally designed for Hg 2+ detection, which was facially prepared via one‐step reaction at room temperature. The formation of Hg−S bond between Hg 2+ and MTG inhibited the decomposition ability of MTG toward MnO2 nanosheets, thus resulting in a color change from colorless to brown. On this basis, the probe quantified Hg 2+ in the concentration range from 2 to 60 μM with a low detection limit of 0.75 μM. The probe was applied to the detection of Hg 2+ in tap water successfully, and was further fabricated into test strips for the convenience of use. Thereby, a simple and sensitive colorimetric probe for Hg 2+ is developed in this work, which holds future promise for monitoring Hg 2+ in the environment. Abstract : In this work, a simple and sensitive colorimetric probe was developed for the detection of Hg 2+ based on MnO2 nanosheets and monothioglycerol, which holded future promise for monitoring the concentration of Hg 2+ in the environment. The mechanism relied that the formation of Hg−S bond between Hg 2+ and MTG inhibited the decomposition ability of monothioglycerol toward MnO2 nanosheets, resulting in a color change from colorless to brown.